2020
DOI: 10.1097/gox.0000000000002752
|View full text |Cite
|
Sign up to set email alerts
|

Lateral and Inferior Implant Malposition in Prosthetic Breast Reconstruction: Incidence and Risk Factors

Abstract: Background: Implant malposition is one of the most common causes for revision after prosthetic breast reconstruction. There is a paucity of research on the incidence, etiology and risk factors for implant malposition in this setting. Methods: Retrospective review of a single surgeon’s prosthetic breast reconstructions was performed. Variables collected included age, BMI, radiation, chemotherapy, implant characteristics and malposition location (inferior or lateral). Binary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…The rate of capsular contraction in the literature without fat grafting in the setting of PMRT and alloplastic reconstruction ranges from 12.5% to 53.3%. 22 Our reported implant malposition rate of 9.8% is similar to implant malposition rates in breast reconstruction without radiation quoted from 5% to 9.8% 23 , 24 and much lower compared with a malposition rate of 27.8% in the context of radiation. 25 …”
Section: Discussionsupporting
confidence: 79%
“…The rate of capsular contraction in the literature without fat grafting in the setting of PMRT and alloplastic reconstruction ranges from 12.5% to 53.3%. 22 Our reported implant malposition rate of 9.8% is similar to implant malposition rates in breast reconstruction without radiation quoted from 5% to 9.8% 23 , 24 and much lower compared with a malposition rate of 27.8% in the context of radiation. 25 …”
Section: Discussionsupporting
confidence: 79%
“…Studies have demonstrated that the incidence of implant displacement in prepectoral reconstruction is ∼5.9% 2 and in subpectoral breast reconstruction is ∼9.8%. 3 As a means of overcoming these compressive forces, overfilling of tissue expanders was often necessary with subpectoral placement. These compressive forces were exacerbated following radiation therapy due to the progressive fibrosis of the pectoralis major muscle and the overlying adipocutaneous layer.…”
mentioning
confidence: 99%